Vitamin D status in outpatient department patients: a retrospective study - Chhetri, Niru; Chhetri, Ajit; Bhattacharya, Gora Chand; Mukherjee, Arati; Sen, Sandip; Kumar, Abhay (International Journal of Research in Medical Sciences, 2017)
Background: Although there are innumerable studies on vitamin D deficiency in India, there is limited data in Eastern Bihar and North Bengal. Keeping this in view, the aim of our study is to find out the prevalence of vitamin D deficiency in our region. Methods: Patients attending the outpatient departments (OPDs) in MGM Medical College, Kishanganj, Bihar, India and Medica North Bengal Clinic, Siliguri, West Bengal (January 2014 to December 2015) for various ailments and who were advised vitamin D estimation were included in our study. Results: Out of 485 patients, 187 were male and 298 were female. Age of the study population ranged from 1 month to 83 years. Maximum number of patients was in the age group of 21 to 60 years. Vitamin D deficiency was seen in 74.44 % out of which 54.22% had frank deficiency and 20.22% had insufficient levels with 46.4% female and 28.04% male subject. Conclusions: Prevalence of vitamin D deficiency is very high in our region that is in Eastern Bihar and North Bengal, as is reflected from our study. This is the pattern seen in other parts of our country too. Also, the deficiency is high in the age group 21 to 60 years and females outnumber the male.